Immunological response to Mycobacterium avium subsp. paratuberculosis in chickens - Chui, Linda W. (Canadian Veterinary Medical Association, 2004)
Enzyme-linked immunosorbent assay (ELISA) and culture are 2 common diagnostic tests for detecting Mycobacterium avium subsp. paratuberculosis (Map) in Johne’s disease, but they are not as sensitive as polymerase chain reaction (PCR). However, inhibitors can coextract with the target DNA and cause interference in PCR. Development of an immune capture assay followed by PCR amplification can alleviate this problem. In this study, we were able to induce an immune response in chickens using heat or formalin inactivated Map. The purified immunoglobulin (Ig)Y has a molecular weight of 160 kDa. The titers were at 1:6400 and 1:12 800 at weeks 5 to 6 and 8 to 9, respectively, as determined by the IDEXX modified ELISA kit for Johne’s disease. The IgY produced from inactivated bacterial cells had no effect on its ability to recognize live Map cells as illustrated by immunofluorescence assay and immune capture PCR results.